Psychological Mechanisms of Decision Making In Athletes - Safoev Hasan Aminovich (Jurnal Psikologi, 2025)
This article examines the psychological mechanisms of decision-making in athletes, including the influence of cognitive, emotional, and personality factors on the process of choosing the optimal decision in sports activities. The study analyzes key aspects such as intuitive and analytical thinking, stress resistance, impulsivity, motivation, and the ability to adapt in conditions of high uncertainty. Special attention is given to how different types of temperament and the level of professional experience of an athlete determine their ability to make quick and accurate decisions in competitive conditions.